Effect of nano SiC addition on mechanical properties of Al-Nano SiC composite materials SS304 woven wire using stir casting method - Alfi Hasan; Pieter Muhammad Iko Marrendra; Salahuddin Junus; Mahros Darsin (Politeknik Negeri Lhokseumawe, 2023)
The wide variety of applications in various industries, such as automotive, aerospace, construction, and electronics, aluminum is one of the metals that needs to improve its mechanical properties. This study aims to determine the effect of adding reinforcing powder using the stir casting method on the mechanical properties of the Al-nano SiC/SS304 Wire Woven Composite material. The method used in this study is an experiment with the addition of a matrix to the composite material. The addition of nano metal was carried out to modify the mechanical properties of the aluminum material. Variation of the composition of each specimen using the volume fraction of nano-SiC (1%, 3%, 5%) and 4% Mg and the addition of woven SS304 wire on the tensile strength and hardness tests. The highest tensile test results for the 5% volume fraction variation were 149 MPa and the hardness test was obtained at 69 HRB for the 5% volume fraction variation